2022
DOI: 10.4314/tzool.v20i1.14
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of the mona monkey, Cercopithecus mona (Schreber, 1774) and anthropogenic threats in selected areas of Lagos State, Nigeria

Abstract: The mona monkey (Cercopithecus mona) is the major non-human primate adapted to swamp forests that characterizes Lagos State. It is useful in ecological services as seed disperser and reforestation. Efforts to legally conserve this species have been ineffective due to non-enforcement of conservation laws. This study determined the population estimate and threats to C. mona in order to provide useful information for its conservation in Lagos State. Using total head count and questionnaires, the occurrence, abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 16 publications
2
5
1
Order By: Relevance
“…The mona monkeys' diet in the dry and wet seasons is mainly made up of fruits (mature and immature), followed by seeds. This finding supports previous studies about the frugivorious diet of the species (Matsuda Goodwin 2007, Ejidike andSalawu 2009;Olaleru et al 2020). Fruits provide mainly carbohydrates and energy to primates (Riba-Hernandez et al 2003).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The mona monkeys' diet in the dry and wet seasons is mainly made up of fruits (mature and immature), followed by seeds. This finding supports previous studies about the frugivorious diet of the species (Matsuda Goodwin 2007, Ejidike andSalawu 2009;Olaleru et al 2020). Fruits provide mainly carbohydrates and energy to primates (Riba-Hernandez et al 2003).…”
Section: Discussionsupporting
confidence: 91%
“…The mona monkey consumed parts of 22 plant species during both dry and wet seasons. The species richness found in this study was lower than the 31 species reported by Olaleru et al (2020) in Okomu National Park, Nigeria. Some species, such as Pycnanthus angolensis, Raphia hookeri, Xylopia aethiopica, etc.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations